Living and dead benthic foraminiferal distribution in two areas of the Ross Sea (Antarctica) - Capotondi, Lucilla; Bonomo, Sergio; Budillon, Giorgio; Giordano, Patrizia; Langone, Leonardo (Atti della Accademia nazionale dei Lincei. Rendiconti Lincei. Scienze fisiche e naturali, 2020)
We investigated the living (stained) and dead benthic foraminiferal assemblages collected in surface sediment samples (0–1 cm) from two different areas (JOIDES Basin and Mawson Bank) of the Ross Sea (Antarctica). Samples were collected during the BEDROSE oceanographic cruise from January to February 2017. Four living and dead benthic foraminiferal fauna assemblages have been distinguished based on cluster analysis. The differences observed in the living and dead foraminiferal content from the two investigated areas are the result of taphonomic processes induced by the different oceanographic settings and environmental conditions. In the JOIDES Basin, agglutinated taxa Rhabdamminella cylindrica, Lagenammina difflugiformis, Adercotryma glomeratum, Recurvoides contortus, Reophax subfusiformis with high percentages of Trochammina group and Reophax spiculifer associated with the calcareous species Nonionella bradii and Astrononion echolsi characterize the living assemblages. The comparison between living and dead benthic foraminifera reveals considerable similarities in terms of the presence/absence of agglutinated species and differences in relative abundance of calcareous taxa. However, the major influencing factor in foraminiferal preservation appears to be the carbonate dissolution. Results from Mawson Bank show an almost exclusive presence of calcareous taxa with high percentages of Globocassidulina group in both living and dead assemblages. The dead fauna assemblage differs from the corresponding living assemblage by being more diverse documenting high-energy current influence on marine sedimentation. Graphic abstract